Anti-hyperglycemic property of Hericium erinaceus – A mini review - Chaiyavat Chaiyasut (2018)
© 2017 Hainan Medical University Hericium erinaceus (H. erinaceus) is one of the widely used edible mushrooms around the world, primarily in Asian countries. H. erinaceus is used in traditional medicines, and mushroom based foods. The fruiting body and mycelia of H. erinaceus are extracted using the solvents, and several bioactive compounds were identified. Several studies have reported that those bioactive compounds exhibit many health benefits such as hemagglutinating, antimicrobial, immunomodulatory, antitumor, antioxidant, and anti-aging activities, etc. This manuscript consciously updated the information about the composition of H. erinaceus, H. erinaceus based foods, and anti-hyperglycemic property of H. erinaceus.